Click Chemistry Approach to Isoindole-1,3-dione Tethered 1,2,3-Triazole Derivatives - Kaur, Rajneesh; Singh, Raman; Kumar, Antresh; Singh, Kuldeep (SynOpen, 2019)
A convenient and efficient approach for the synthesis of novel 1,2,3-triazole tethered isoindol-1,3-dione conjugates by a nucleophilic substitution reaction of phthalic anhydride with 1,2,3-triazole containing carbohydrazide is described. The latter were prepared by using click chemistry.
Keywords: amidiaztion; hydrazinolysis; carbohydrazide; carboxamide; click chemistry